A revision of the genus Thouarella Gray, 1870 (Octocorallia: Primnoidae), including an illustrated dichotomous key, a new species description, and comments on Plumarella Gray, 1870 and Dasystenella, Versluys, 1906. - Taylor, M; Cairns, S; Agnew, D; Rogers, A (2013)
A comprehensive revision of the genus Thouarella is presented. Thirty-five holotypes of the 38 nominal Thouarella species, two varieties, and one form were examined. The number of original Thouarella species has been reduced to 25, mostly through synonymy or new genus combinations. In the process several new species have also been identified, one of which is described here as Thouarella parachilensis nov. sp. The genus is split into two groups based on polyp arrangement: Group 1 with isolated polyps and Group 2 with polyps in pairs or whorls. An illustrated dichotomous key and detailed character table of the 25 Thouarella species are presented alongside an up-to-date account of all species described in the 19th and 20th centuries and summaries of the few described from 2000 onwards. We propose that Thouarella longispinosa is synonymous with Dasystenella acanthina, T. versluysi with T. brucei, and, T. tenuisquamis, T. flabellata, and T. carinata are synonymous with T. laxa. Lastly, we propose that T. bayeri and T. undulata be placed in Plumarella and support recent suggestions that T. alternata, T. recta, T. superba, and T. diadema are also Plumarella.